2007
DOI: 10.1103/physrevb.76.075107
|View full text |Cite
|
Sign up to set email alerts
|

Correlation potential in density functional theory at the GWA level: Spherical atoms

Abstract: As part of a project to obtain better optical response functions for nano materials and other systems with strong excitonic effects we here calculate the exchange-correlation (XC) potential of density-functional theory (DFT) at a level of approximation which corresponds to the dynamicallyscreened-exchange or GW approximation. In this process we have designed a new numerical method based on cubic splines which appears to be superior to other techniques previously applied to the "inverse engineering problem" of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 45 publications
1
119
0
Order By: Relevance
“…This basis set has shown to be ideally suited for solving the LSS equation, 4 an equation known to be numerically unstable when using other methods and basis functions. 31,32,33,34,35 We have here found that cubic splines also provide an efficient method for solving the equation for f x .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This basis set has shown to be ideally suited for solving the LSS equation, 4 an equation known to be numerically unstable when using other methods and basis functions. 31,32,33,34,35 We have here found that cubic splines also provide an efficient method for solving the equation for f x .…”
Section: Methodsmentioning
confidence: 99%
“…If the density is that given by EXX we have selfconsistency and the resulting f x is that presented here. If we instead start with a better density, much closer to the exact one, the corresponding eigenvalue differences will be much closer to real particle-hole excitation energies 4 and we will obtain an f x which will still obey the f -sum rule while giving rise to an optical spectrum with a continuum starting in almost the correct place -because the highest occupied exact DF eigenvalue equals the the negative of the ionization potential. 30 This topic is further discussed together with numerical results in Sec.…”
Section: B Tdexx As Compared To Tdhfmentioning
confidence: 99%
See 1 more Smart Citation
“…In chemical physics, cubic spline interpolation has been applied as a basis to solve a complex differential and integral Schrödinger [13][14][15], Dirac [16], and Sham-Schlüter equations [17], Thomas-Fermi model [18], in calculations of vibrational and rotational spectra [19] and many other cases [20][21][22][23][24][25][26][27][28][29][30][31][32]. Since the derivatives of third and higher order polynomials are discontinuous, cubic spline interpolation is limited to applications that are not sensitive to the smoothness of derivatives higher than second order.…”
Section: Introductionmentioning
confidence: 99%
“…The first is to constrain the types of G 0 or U xc being considered based on physical knowledge or intuition. For example, it is known that forcing U xc to be a local potential is sufficient to create a minimum for the Klein functional [32,36,37]. However, a local potential can not directly and consistently describe a number of simple non-local effects, e.g., Fock exchange which automatically removes problematic electron self-interaction effects.…”
Section: Baym-kadanoff Approachmentioning
confidence: 99%